THU0373 Pamidronate Treatment of SAPHO Syndrome: A Retrospective Study of 22 Cases. (10th June 2014) - Delattre, E.; Guillot, X.; Prati, C.; Wendling, D.
Abstract : Background: There are no guidelines for the treatment of SAPHO (Synovitis, Acne, Pustulosis, Osteitis, Hyperostosis) syndrome, particularly in the situation of inadequate response to NSAIDs. Bone involvement (hyperostosis, osteitis) may legitimate the therapeutic use of bisphosphonates. Objectives: The aim of this study was to evaluate efficacy and tolerance of intravenous (IV) pamidronate in patients with SAPHO. Methods: Open monocentric retrospective study including patients with SAPHO syndrome (Benhamou "criteria") and treated with IV pamidronate. Main characteristics of the disease and the treatments were recorded. Pamidronate was administered IV, 60 or 120 mg (one or 2 infusions), eventually repeated evey 4 weeks. Efficacy was assessed by global patient VAS, % of improvement, physician's judgment and biologic parameters (ESR, CRP). Side effects were recorded. Results: 22 patients were evaluable: 19 women, mean age 48 years, mean disease duration 5.8 years. Skin involvement was present in 18 patients, 22 patients had osteitis, 4 hyperostosis and 13 a sterno clavicular involvement. Initial CRP was 16±22 mg/l, ESR 25 and VAS 67±21 mm. The mean number of infusions was 5.6 (1 to 23). A significant improvement is obvious at month 1 (VAS 44±18; p=0.01), no more significative at month 2 (p=0.06). Physician's judgment was: efficacy (n=13), partial or transient efficacy (n=8), inefficacy (n=1). In case of efficacy, the mean duration of efficacy under treatment was 7 months. A non significant decrease in ESR was observed at month 1 (25 to 14 mm). Side effects were noted in 11 cases: flu-like syndrome (N=5), fever (3), hypocalcemia, conjunctivitis, headache, vein inflammation. No predictive factor for good response could be found in these patients. Conclusions: This study suggests a modest global efficacy, variable and transitory, of IV pamidronate treatment in SAPHO syndrome. Analysis of the results remains difficult in the absence of validated response criteria in this heterogeneous disease. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1582